강원 횡성 및 제주지역 더덕밭 잡초발생양상 - 송희근(Hee Geun Song); 김창석(Chang-Seok Kim); 이정란(Jeongran Lee); 서현아(Hyun-A Seo); 최경미(Kyung Mi Choi); 이인용(In-Yong Lee) (Weed & turfgrass science, 2015)
The weed flora in the Codonopsis lanceolata upland fields were surveyed in Hoengseong and Jeju in May, August, and October of 2014. The objectives of this study were to use the survey data for establishing weed control methods and to bring awareness of possible problematic weeds occurred in C. lanceolata upland fields in Korea. Altogether 207 weed species of 47 families were identified, of which 87 were annual, 47 species were biennial and 73 were perennial. Based on the morphological characteristic of the leaves, 182 species were broad leaves, 18 species were grasses, and 7 species were sedges. The dominance was highest in the Artemisia princeps followed by Digitaria ciliaris, Commelina communis, Persicaria longiseta and Echinochloa crus-galli etc. Fifty-nine species were exotic weeds with 29% of a total presence, of which Erigeron annuus was highest, followed by Crassocephalum crepidioides, Bidens frondosa, Hypochaeris radicata etc. In the PCA plot, weeds presented in the C. lanceolata upland fields of Hoengseong were divided into three groups, E. annuus, Sigesbeckia pubescence and C. communis communities and those of Jeju were divided into four groups, C. crepidioides-Cyperus iria, Spergula arvensis, Poa annua and Youngia japonica communities. 강원 횡성 및 제주 지역의 더덕밭에 발생하는 잡초 발생상황을 파악하여 더덕밭 잡초방제의 기초자료로 활용하기 위하여 2014년 5월부터 10월까지 총 3회 조사하였다. 더덕 밭에서 발생하는 잡초는 47과 207종으로 일년생잡초가 87종, 월년생잡초가 47종, 그리고 다년생잡초가 73종이었다. 잡초의 형태적 특성에 따른 분류에서 광엽잡초는 182종, 화본과잡초는 18종, 사초과잡초는 7종이었다. 우점도가 높은 잡초는 쑥, 바랭이, 닭의장풀, 개여뀌, 돌피 등이었다. 더덕밭 발생잡초 중 외래잡초가 59종으로 전체의 29%를 차지하였으며, 개망초, 주홍서나물, 미국가막사리, 서양금혼초 등이 발생하였다. PCA 분석 결과, 강원 횡성 더덕밭의 잡초군락은 개망초군락, 털진득찰군락과 닭의장풀군락으로 분석되었으며, 제주 더덕밭의 잡초군락은 주홍서나물-참방동사니군락, 들개미자리군락, 새포아풀군락과 뽀리뱅이군락으로 분석되었다.